An AHP/DEA ranking method based on service quality approach: a case study in hotel industry. (1st January 2013) - Shirouyehzad, Hadi; Lotfi, Farhad Hosseinzadeh; Arabzad, S. Mohammad; Dabestani, Reza
For appropriate decision making in organisations, it is particularly important to identify strengths and weakness of the organisations and also their status versus other organisations. Understanding one's status in comparison with others can be effective and may lead to decision-making improvement. There are a number of criteria for evaluating, ranking and analysing efficiency of organisations. One of the most important approaches in service organisations is service quality, which evaluates the customer satisfaction from delivered services. In this paper, an integrated method based on AHP and DEA is presented to rank service units considering service quality dimensions. The proposed DEA model includes five service quality gaps as inputs and customers' perceptions as single output. A pair-wise comparisons questionnaire is filled by experts to determine the weights of inputs criteria. Finally, hotels' ranking are determined based on the proposed integrated AHP/DEA model and service quality approach.